2013
DOI: 10.1103/physrevlett.111.027204
|View full text |Cite
|
Sign up to set email alerts
|

Single Domain Spin Manipulation by Electric Fields in Strain Coupled Artificial Multiferroic Nanostructures

Abstract: We demonstrate in situ 90° electric field-induced uniform magnetization rotation in single domain submicron ferromagnetic islands grown on a ferroelectric single crystal using x-ray photoemission electron microscopy. The experimental findings are well correlated with micromagnetic simulations, showing that the reorientation occurs by the strain-induced magnetoelectric interaction between the ferromagnetic nanostructures and the ferroelectric crystal. Specifically, the ferroelectric domain structure plays a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
192
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 22 publications
8
192
0
3
Order By: Relevance
“…Similar effect can be observed in Py/YMO herterostructure as well [31]. In 2013, Buzzi et al [32] observed a 90° rotation of magnetization due to the switching of out-of-plane ferroelectric polarization in artificial multiferroic nanostructures (arrays of Ni on PMN-PT substrates). The magnetization rotation was non-volatile and reversible.…”
Section: Science China Materialssupporting
confidence: 53%
“…Similar effect can be observed in Py/YMO herterostructure as well [31]. In 2013, Buzzi et al [32] observed a 90° rotation of magnetization due to the switching of out-of-plane ferroelectric polarization in artificial multiferroic nanostructures (arrays of Ni on PMN-PT substrates). The magnetization rotation was non-volatile and reversible.…”
Section: Science China Materialssupporting
confidence: 53%
“…[27][28][29][30] There are also several theoretical predications 31-33 that such a method will dissipate only a few atto-Joules (aJ) of energy to write data. This establishes the promise of using strain to control the resistance of an MTJ for ultra-energy-efficient memory applications.…”
Section: -21mentioning
confidence: 99%
“…[16][17][18][19][20][21] It has been widely investigated in various piezoelectric/ferromagnetic bilayer thin films [22][23][24][25][26] or nano-structures. [27][28][29][30] There are also several theoretical predications [31][32][33] that such a method will dissipate only a few atto-Joules (aJ) of energy to write data. This establishes the promise of using strain to control the resistance of an MTJ for ultra-energy-efficient memory applications.…”
mentioning
confidence: 99%
“…Note that the scale of magnetic island is down to 100 nm, which makes both the fabrication and characterization difficult. Moreover, the evolution of magnetization under electric fields for nanomagnet depends strongly on the FE domain state below it 32,61 and is different from that of the continuous FM film. 21,23,56 Despite all this, experimental realization of this proposition will be an important progress for the purely electrical modulation of magnetism and for new generation of spintronic devices.…”
mentioning
confidence: 99%